The Early Miocene Critical Zone at Karungu, Western Kenya: An Equatorial, Open Habitat with Few Primate Remains - Lukens, William E.; Lehmann, Thomas; Peppe, Daniel J.; Fox, David L.; Driese, Steven G.; McNulty, Kieran P. (Frontiers in Earth Science, 2017)
Early Miocene outcrops near Karungu, Western Kenya, preserve a range of fluvio-lacustrine, lowland landscapes that contain abundant fossils of terrestrial and aquatic vertebrates. Primates are notably rare among these remains, although nearby early Miocene strata on Rusinga Island contain a rich assemblage of fossilized catarrhines and strepsirrhines. To explore possible environmental controls on the occurrence of early Miocene primates, we performed a deep-time Critical Zone (DTCZ) reconstruction focused on floodplain paleosols at the Ngira locality in Karungu. We specifically focused on a single stratigraphic unit (NG15), which preserves moderately developed paleosols that contain a microvertebrate fossil assemblage. Although similarities between deposits at Karungu and Rusinga Island are commonly assumed, physical sedimentary processes, vegetative cover, soil hydrology, and some aspects of climate state are notably different between the two areas. Estimates of paleoclimate parameters using paleosol B horizon elemental chemistry and morphologic properties are consistent with seasonal, dry subhumid conditions, occasional waterlogging, and herbaceous vegetation. The reconstructed small mammal community indicates periodic waterlogging and open-canopy conditions. Based on the presence of herbaceous root traces, abundant microcharcoal, and pedogenic carbonates with high stable carbon isotope ratios, we interpret NG15 to have formed under a warm, seasonally dry, open riparian woodland to wooded grassland, in which at least a subset of the vegetation was likely C4 biomass. Our results, coupled with previous paleoenvironmental interpretations for deposits on Rusinga Island, demonstrate that there was considerable environmental heterogeneity ranging from open to closed habitats in the early Miocene. We hypothesize that the relative paucity of primates at Karungu was driven by their environmental preference for locally abundant closed canopy vegetation, which was likely absent at Karungu, at least during the NG15 interval if not also earlier and later intervals that have not yet been studied in as much detail.